Temporal lobe regions essential for preserved picture naming after left temporal epilepsy surgery. (11th August 2020) - Binder, Jeffrey R.; Tong, Jia‐Qing; Pillay, Sara B.; Conant, Lisa L.; Humphries, Colin J.; Raghavan, Manoj; Mueller, Wade M.; Busch, Robyn M.; Allen, Linda; Gross, William L.; Anderson, Christopher T.; Carlson, Chad E.; et al.
Abstract: Objective: To define left temporal lobe regions where surgical resection produces a persistent postoperative decline in naming visual objects. Methods: Pre‐ and postoperative brain magnetic resonance imaging data and picture naming (Boston Naming Test) scores were obtained prospectively from 59 people with drug‐resistant left temporal lobe epilepsy. All patients had left hemisphere language dominance at baseline and underwent surgical resection or ablation in the left temporal lobe. Postoperative naming assessment occurred approximately 7 months after surgery. Surgical lesions were mapped to a standard template, and the relationship between presence or absence of a lesion and the degree of naming decline was tested at each template voxel while controlling for effects of overall lesion size. Results: Patients declined by an average of 15% in their naming score, with wide variation across individuals. Decline was significantly related to damage in a cluster of voxels in the ventral temporal lobe, located mainly in the fusiform gyrus approximately 4‐6 cm posterior to the temporal tip. Extent of damage to this region explained roughly 50% of the variance in outcome. Picture naming decline was not related to hippocampal or temporal pole damage. Significance: The results provide the first statistical map relating lesion location in left temporal lobe epilepsy surgery to picture naming decline, and they support previous observations of transient naming deficits from electrical stimulation in the basal temporal cortex. The critical lesion is relatively posterior and could be avoided in many patients undergoing left temporal lobe surgery for intractable epilepsy.